Tingkat Kesulitan Mahasiswa dalam Memahami Mata Kuliah Pengantar Dasar Matematika di Prodi Pendidikan Matematika FPMIPA IKIP PGRI Bali: Level of Difficulty of Students in Understanding Subjects of Introduction to Basic Mathematics in Mathematical Education Products FPMIPA IKIP PGRI Bali - Ni Wayan Sunita; N Putri Sumaryani (Emasains : Jurnal Edukasi Matematika dan Sains, 2019)
This study aims to determine the level of student learning difficulties in the Introduction to Basic Mathematics courses in the mathematics education study program FPMIPA IKIP PGRI Bali. This type of research is based on the formulation of research problems, so this study is categorized into descriptive research types. This is intended to manage the data obtained from respondents based on the results of interviews conducted by researchers. The research subjects were mathematics education study program students who had completed the subjects of introductory to basic mathematics in this case were students of the 2017 class. Based on the results and discussion it could be concluded that the level of difficulty of students in understanding the subjects of introductory to basic mathematics in the Mathematics Education Study Program of FPMIPA IKIP PGRI Bali was high.